Global prevalence of myasthenia gravis and the effectiveness of common drugs in its treatment: a systematic review and meta-analysis - Salari, Nader; Fatahi, Behnaz; Bartina, Yalda; Kazeminia, Mohsen; Fatahian, Reza; Mohammadi, Payam; Shohaimi, Shamarina; Mohammadi, Masoud (BioMed Central, 2021)
Background: Myasthenia gravis is a neuromuscular autoimmune disorder characterized by weakness and disability in the voluntary muscles. There have been several preliminary studies on the epidemiology of myasthenia gravis in different parts of the world and the effectiveness of common drugs in its treatment, but there has been no comprehensive study of the efficacy of common drugs in the treatment of myasthenia gravis. Therefore, this study aimed to determine the epidemiology of myasthenia gravis globally and the effectiveness of common drugs in its treatment using systematic review and meta-analysis.